Bacterial Lipoteichoic Acid Attenuates Toll-Like Receptor Dependent Dendritic Cells Activation and Inflammatory Response - Suguru Saito; Alato Okuno; Duo-Yao Cao; Zhenzi Peng; Hui-Ya Wu; Shu-Hui Lin (Pathogens, 2020)
Toll-like receptor (TLR) signaling is an indispensable factor in immune cells activation. Many TLR ligands have been identified, and were characterized the immunological functions such as inflammatory cytokine production in immune cells. However, the anti-inflammatory response in TLR ligand-mediated manner is poorly understood. In this report, we show that bacterial lipoteichoic acid (LTA), which is a TLR2 ligand from gram-positive bacteria including Staphylococcus aureus (S. aureus), suppresses TLR-mediated inflammatory response in dendritic cells (DCs). The TLR ligand-induced Tumor Necrosis Factor-alpha (TNF-α) production was suppressed in the bone marrow derived dendritic cells (BMDCs) by co-treatment of LTA. The cellular activation, which was characterized as upregulations of CD80, CD86 and major histocompatibility complex II (MHC II) expression, was also suppressed in the TLR ligand stimulated BMDCs in the presence of LTA. While LTA itself didn’t induced both TNF-α production and upregulation of cell surface markers. The LTA mediated immunosuppressive function was abolished by TLR2 blocking in lipopolysaccharide (LPS)-stimulated BMDCs. Furthermore, LTA also showed the immunosuppressive function in the generation of IFN-γ+CD4+ T (Th1) cells by attenuation of antigen presenting activity in the BMDCs. In the imiquimod (IMQ)-induced acute skin inflammation, LTA suppressed the inflammation by downregulation of the activation in skin accumulated DCs. Thus, LTA is a TLR2 dependent immunological suppressor against inflammatory response induced by other TLR ligands in the DCs.